Ad Hoc Networks 6th International ICST Conference, ADHOCNETS 2014, Rhodes, Greece, August 18-19, 2014, Revised Selected Papers - Mitton, Natalie; Gallais, Antoine; Kantarci, Melike Erol.; Papavassiliou, Symeon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed proceedings of the 6th International Conference on Ad Hoc Networks, ADHOCNETS 2014, held in Rhodes, Greece, in August 2014. The 16 regular and invited papers presented were carefully selected and reviewed from numerous submissions and cover a wide range of applications, such as mobile ad hoc networks, sensor networks, vehicular networks, intelligent transportation systems, wireless sensor networks security.
Interest-based forwarding for satisfying user preferences in vehicular networks -- Traffic-Aware Access-Points Deployment Strategies for VANETS -- A Social-based Approach for Message Dissemination in Vehicular Ad Hoc Networks -- Intelligent Transportation Systems - Maybe, But Where Are My Agents -- On the usefulness of information hiding techniques for wireless sensor networks security -- Evaluation of Malware Spreading in Wireless Multihop Networks with Churn -- Security and Privacy-preserving Mechanism for Aggregator based Vehicle-to-Grid Network -- An Improved TCP for Reduced Packet Delay in IEEE 802.11s-based Smart Grid AMI Networks -- A Cluster-based and On-demand routing algorithm for Large-Scale Multi-hop Wireless Sensor Networks -- Social OLSR: A social based routing algorithm for Mobile Ad Hoc Networks -- Improving Stability in QoS Routing for Ad-Hoc Networks -- Content Centricity in Constrained Cellular-Assisted D2D Communications -- Adaptive Transmit Power Adjustment Technique for ZigBee Network under Wi-Fi Interference -- Channel Switching Cost-Aware Resource Allocation for Multi-hop Cognitive Radio Networks with a Single Transceiver -- Connectivity Provisioning Using Cognitive Channel Selection in Vehicular Networks -- Using location services to autonomously drive flying mobile sinks in Wireless Sensor Networks -- Validation and Evaluation of the Chosen Path Planning Algorithm for Localization of Nodes Using an Unmanned Aerial Vehicle in Disaster Scenarios -- Structural Health Monitoring of Infrastructure using Wireless Sensor System -- A low-overhead localized target coverage algorithm in wireless sensor networks -- Connectivity restoration and amelioration in wireless ad-hoc networks: A practical solution.
Keywords: Computer science; Computer communication systems; Special purpose computers; Computer security; Computer Science; Computer Science, general; Computer Communication Networks; Special Purpose and Application-Based Systems; Systems and Data Security; Electronic books